Knowledge atlas of antibody-drug conjugates on CiteSpace and clinical trial visualization analysis - Yao, Peizhuo; Zhang, Yinbin; Zhang, Shuqun; Wei, Xinyu; Liu, Yanbin; Du, Chong; Hu, Mingyou; Feng, Cong; Li, Jia; Zhao, Fang; Li, Chaofan; Li, Zhen; et al. (Frontiers in Oncology, 2023)
Objective: Antibody-drugs conjugates(ADCs) is a novel drug with highly targeted and tumor-killing ability and developing rapidly. This study aimed to evaluate drug discovery and clinical trial of and explore the hotspots and frontiers from 2012 to 2022 using bibliometric methods. Methods: Publications on ADCs were retrieved between 2012 and 2022 from Web of Science(WoS) and analyzed with CiteSpace 5.8.R3 software for the time, region, journals, institutions, etc. Clinical trial were downloaded from clinical trial.org and visualized with excel software. Results: A total of 679 publications were obtained, and 187 drug trial were retrieved. Since 2012, the researches of ADCs increased year by year. Since 2020, the researches related to ADCs have rise sharply, and the annual relevant number of relevant documents has exceeded 100 for the first time. The main countries and regions for the publication and clinical research of ADCs are the United States, Asian countries including China, Japan, South Korea, and European countries including Italy, Britain, Spain, France, Belgium, among which the United States is the most authoritative and superior. The main targets of ADCs are HER2, EGFR, CD30, Trop-2, CD22, lectin-2, BCMA and CD79. Several ADCs obtained excellent clinical rusults and approved by FDA in breast cancer, lymphoma and urogenital tumor. More ADCs were registering Clinical studies and clinical phase I and clinical phase II were on going to explore new indications in lung cancer, gastirc cancer and ovarian cancer.. Conclusion: In recent years, new ADCs drugs have achieved excellent success and attracted the attention of global enterprises and institutions. Countries around the world have developed new ADCs drugs and conducted clinical research in various tumors. In the future, more ADCs will gradually enter the clinic and change the practice of tumor diagnosis and treatment.